Corrosion and bioactivity performance of graphene oxide coating on Ti Nb shape memory alloys in simulated body fluid - Saud, S.N.; Raheleh Hosseinian, S.; Bakhsheshi-Rad, H.R.; Yaghoubidoust, F.; Iqbal, N.; Hamzah, E.; Ooi, Chong Heng Raymond (Elsevier, 2016)
In the present work, the microstructure, corrosion, and bioactivity of graphene oxide (GO) coating on the laser-modified and -unmodified surfaces of TiNb shape memory alloys (SMAs) were investigated. The surface morphology and chemical composition was examined using field emission scanning electron microscopy (FE-SEM) and X-ray diffraction (XRD). The surface modification was carried out via a femtosecond laser with the aim to increase the surface roughness, and thus increase the adhesion property. FE-SEM analysis of the laser-treated Ti-30 at.% Nb revealed the increase in surface roughness and oxygen/nitrogen containing groups on the Ti-30 at.% Nb surface after being surface modified via a femtosecond laser. Furthermore, the thickness of GO was increased from 35 μm to 45 μm after the surface was modified. Potentiodynamic polarisation and electrochemical impedance spectroscopy studies revealed that both the GO and laser/GO-coated samples exhibited higher corrosion resistance than that of the uncoated TiNb SMA sample. However, the laser/GO-coated sample presented the highest corrosion resistance in SBF at 37 °C. In addition, during soaking in the simulated body fluid (SBF), both the GO and laser/GO coating improved the formation of apatite layer. Based on the bioactivity results, the GO coating exhibited a remarkable antibacterial activity against gram-negative bacteria compared with the uncoated. In conclusion, the present results indicate that Ti-30 at.% Nb SMAs may be promising alternatives to NiTi for certain biomedical applications.